Ca isotopic compositions of zoned granitoid intrusion: Implications for the emplacement and evolution of magma bodies. (1st June 2022) - Liu, Fang; Zhang, Zhaofeng; Zhang, Zhekun; Li, Xin; Yang, Di
Abstract: To investigate the mechanism of magma emplacement of the intruded zoned pluton, we report high-precision Ca isotopic data of 23 granitoids (including granodiorite and quartz diorite), 5 mafic enclaves, and 7 hornblende and plagioclase mineral pairs from the Early Cretaceous Fangshan pluton, Beijing, China. Δ 44/40 CaHbl-Pl of rocks span from 0.02 ± 0.15‰ to 0.23 ± 0.12‰, which likely reflects equilibrium inter-mineral isotope fractionation. The granodiorites exhibit ∼0.30‰ variation in Ca isotopic compositions, with δ 44/40 Ca ranging from 0.47 ± 0.08‰ to 0.77 ± 0.09‰. The diorites and the enclaves yield δ 44/40 Ca of 0.51 ± 0.03‰ to 0.64 ± 0.05‰, and 0.54 ± 0.06‰ to 0.66 ± 0.11‰, respectively, which are lower than that of the upper continental crust (0.72 ± 0.10‰). Ca isotopic variation cannot be ascribed to K decay due to their low εCa values (< ±1.0). Theoretical study showed that Hbl fractional crystallization could counteract Ca isotope fractionation effect of their co-existing Pl crystallization. Source heterogeneity cannot account for Ca isotopic variation because δ 44/40 Ca does not correlate to ( 87 Sr/ 86 Sr)i . Instead, the Ca isotopic variation is likely controlled by partial melting and residual mineralogy. Specifically, δ 44/40 Ca of the granodiorites are negatively correlated with (Dy/Yb)N, reflecting various magma pools derived from different crustal depths with clinopyroxene and garnet residua. Modeling calculations suggest that the low Ca isotopic signature can be caused by ∼10% partial melting of sources with various proportions of garnet and clinopyroxene (from 5% garnet + 95% clinopyroxene to 40% garnet + 60% clinopyroxene). The diorites intruded earlier than the granodiorites, which can be slightly contaminated by surrounding basement rock. Ca isotopic compositions of enclaves are similar to those of their host rocks. Considering the spatial structure of the Fangshan pluton, it should be assembled by at least four magma pulses derived from various crustal depths through ballooning. Our results show that Ca isotopes can be used as a potential tool to trace magma source depth and decipher the process of magma emplacement of intrusive pluton, which is important to understand the continental crustal growth.